Mediation effects of subjective social status and personality traits between childhood nurturing experiences and depressive symptoms in adult volunteers - Yuki Nakagawa; Miki Ono; Chihiro Morishita; Mina Honyashiki; Yu Tamada; Yota Fujimura; Shinji Higashi; Naoki Hashimoto; Takeshi Inoue; Jiro Masuya (PCN Reports)
Abstract Aim Various risk factors, such as childhood nurturing experiences and subjective social status, have been identified to be involved in the onset of depression. However, the mechanism of depression is not yet fully understood. In this study, we hypothesized that nurturing experienced in childhood affects subjective social status and current personality traits, which in turn influence depressive symptoms in adulthood, and verified this hypothesis through structural equation modeling. Methods A questionnaire survey was conducted on 404 adults. Multiple regression analysis and structural equation modeling were conducted using demographic information and scores for the Patient Health Questionnaire‐9, Parental Bonding Instrument, and NEO Five‐Factor Inventory. Results Subjective social status was found to mediate the association between nurturing experiences and neuroticism (0.029 for Overprotection and –0.034 for Care). On the other hand, neuroticism was found to mediate the association between subjective social status and depressive symptoms (–0.097 in Care model and –0.103 in Overprotection model), as well as the association between nurturing experiences and depressive symptoms (0.144 for Overprotection and –0.134 for Care). Furthermore, it was also shown that complex paths, in which the association of nurturing experiences with depressive symptoms was mediated by two factors, namely, subjective social status and neuroticism, were statistically significant as indirect effects (0.016 for Overprotection and –0.018 for Care). Conclusion In this study, we clarified that nurturing experienced in childhood affects neuroticism in adulthood, which is mediated by subjective social status, and furthermore, the effects of nurturing on neuroticism lead to varying levels of depressive symptoms in adulthood. The mediation effects demonstrated in the present study may contribute towards unraveling the causes of depression and developing effective treatments for depressive symptoms.